Paharpur alias Somapura Mahavihara : a world cultural heritage site - Haque, Enamul, 1936-; International Centre for Study of Bengal Art (Dhaka : The International Centre for Study of Bengal Art, 2014)
A comprehensive volume on Paharpur Site (Somapura Mahavihara), one of the best known Buddhist viharas in the sub-continent.
With 504 illustrations.
Includes bibliographical references and index.
AAL
Complimentary copy from the International Centre for Study of Bengal Art.
In English.
Keywords: Excavations (Archaeology) -- Bangladesh -- Rājshāhi District; Buddhist temples -- Bangladesh -- Rājshāhi District; Buddhist relief (Sculpture) -- Bangladesh -- Rājshāhi District; World Heritage areas -- Bangladesh -- Rājshāhi District; Antiquities -- Collection and preservation; Buddhist relief (Sculpture); Buddhist temples; Excavations (Archaeology); World Heritage areas; Paharpur Site (Bangladesh); Rājshāhi District (Bangladesh) -- Antiquities -- Collection and preservation; Bangladesh -- Paharpur Site; Bangladesh -- Rājshāhi District